Angiotensin II AT(1) receptor blocker candesartan prevents the fast up-regulation of cerebrocortical benzodiazepine-1 receptors induced by acute inflammatory and restraint stress - Sánchez-Lemus, Enrique (2012)
Centrally acting Angiotensin II AT(1) receptor blockers (ARBs) protect from stress-induced disorders and decrease anxiety in a model of inflammatory stress, the systemic injection of bacterial endotoxin lipopolysaccharide (LPS). In order to better understand the anxiolytic effect of ARBs, we treated rats with LPS (50 µg/kg) with or without three days of pretreatment with the ARB candesartan (1 mg/kg/day), and studied cortical benzodiazepine (BZ) and corticotrophin-releasing factor (CRF) receptors. We compared the cortical BZ and CRF receptors expression pattern induced by LPS with that produced in restraint stress. Inflammation stress produced a generalized increase in cortical BZ(1) receptors and reduced mRNA expression of the GABA(A) receptor γ(2) subunit in cingulate cortex; changes were prevented by candesartan pretreatment. Moreover, restraint stress produced similar increases in cortical BZ(1) receptor binding, and candesartan prevented these changes. Treatment with candesartan alone increased cortical BZ(1) binding, and decreased γ(2) subunit mRNA expression in the cingulate cortex. Conversely, we did not find changes in CRF(1) receptor expression in any of the cortical areas studied, either after inflammation or restraint stress. Cortical CRF(2) receptor binding was undetectable, but CRF(2) mRNA expression was decreased by inflammation stress, a change prevented by candesartan. We conclude that stress promotes rapid and widespread changes in cortical BZ(1) receptor expression; and that the stress-induced BZ(1) receptor expression is under the control of AT(1) receptor activity. The results suggest that the anti-anxiety effect of ARBs may be associated with their capacity to regulate stress-induced alterations in cortical BZ(1) receptors.